Dukungan Orang Tua Terhadap Peningkatan Prestasi Atlet Anggar Di Kabupaten Batang (Universitas Negeri Semarang, 2021)
Fencing is a martial art using weapons that has developed into a cultural art of dexterity sports with weapons. In Indonesia, especially in Central Java Province, fencing has reliable athletes, one of which is from Batang Regency. The achievements achieved by an athlete cannot be separated from the support of parents, coaches and the environment. For this reason, the problem of this study is the extent to which parents support the improvement of fencing athletes' performance in Batang Regency. The purpose of this study was to describe and analyze the effect of parental support on fencing athletes in Batang Regency. This research uses quantitative research with data collection techniques in this study using a questionnaire method with descriptive data analysis techniques using IBM Statistic 21. The results of the study are components of parental support such as emotional support, appreciation, information, instrumental have an important influence in terms of improving athlete achievement. Among the four components of parental support, there is one support, namely instrumental support that does not fulfill the requirements to be able to contribute to their children in participating in fencing in Batang.